Mitigation of Enteric Methane Emission through Feed Modification and Rumen Manipulation - Agustin Herliatika; Y Widiawati (Indonesian Center for Animal Research and Development, 2021)
The major of gas emission in the livestock sector are in the form of methane produced by microbial activity in the rumen. The emission of methane cause global warming and is predicted to keep increasing. Feed modification and rumen manipulation are important ways that can be used to mitigate methane emission. Based on this condition, this paper aims to describe several ways to mitigate methane emission using feed and rumen modification for smallholder farmers. Feed modification can be done using high Non-Fiber Carbohydrate (NFC) content in feed and also using balance nutrient feed. Meanwhile, rumen modification can be done through inlcusion of feed additive, microbial products, and oils. Providing feed contains high NFC as much as 21.8-53%DM would decrease methane emission by 3.03-28.33%. While providing feed contains balance nutrients would potentially decrease 21.87% of methane emission. Feed additive addition as much as 0.0011-12%DM decreased 0.59-78% of methane emission. Bacterial inclusion as much as 0.7x108 – 3,6x1011CFU decreased 0- 18.57% of methane emission. Oil or fat inclusion as much as 6%DM decreased 6.02-24.53% of methane emission. A combination of methods can be used to optimize methane mitigation and it can be applicable for farmers to raise their livestock in friendly environment.